Functional Disassociation Between the Protein Domains of MSMEG_4305 of Mycolicibacterium smegmatis (Mycobacterium smegmatis) in vivo - Czubat, Bożena; Minias, Alina; Brzostek, Anna; Żaczek, Anna; Struś, Katarzyna; Zakrzewska-Czerwińska, Jolanta; Dziadek, Jarosław (Frontiers in Microbiology, 2020)
MSMEG_4305 is a two-domain protein of Mycolicibacterium smegmatis (Mycobacterium smegmatis) (Mycolicibacterium smegmatis). The N- terminal domain of MSMEG_4305 encodes an RNase H type I. The C- terminal domain is a presumed CobC, predicted to be involved in the aerobic synthesis of vitamin B12. Both domains reach their maximum at distinct pH, approximately 8.5 and 4.5, respectively. The presence of the CobC domain influenced RNase activity in vitro in homolog Rv2228c. Here, we analyzed the role of MSMEG_4305 in vitamin B12 synthesis and the functional association between both domains in vivo in M. smegmatis. We used knock-out mutant of M. smegmatis, deficient in MSMEG_4305. Whole-cell lysates of the mutants strain contained a lower concentration of vitamin B12, as it determined with immunoenzimatic assay. We observed growth deficits, related to vitamin B12 production, on media containing sulfamethazine and propionate. Removal of the CobC domain of MSMEG_4305 in ∆rnhA background hardly affected the growth rate of M. smegmatis in vivo. The strain carrying truncation showed no fitness deficit in the competitive assay and it did not show increased level of RNA/DNA hybrids in its genome. We show that homologs of MSMEG_4305 are present only in the Actinomycetales phylogenetic branch (according to the old classification system). The domains of MSMEG_4305 homologs accumulate mutations at a different rate, while the linker region is highly variable. We conclude that MSMEG_4305 is a multidomain protein that most probably was fixed in the phylogenetic tree of life due to genetic drift.